Analysis of The Implementation of The One Data Indonesia Policy: Case Studies of The Bandung and Kuningan Regency Governments - Mahadevi, Ayisha (CV. Media Digital Publikasi Indonesia, 2026)
This research aims to compare policy implementation Satu Data Indonesia (SDI) between Bandung Regency with Kuningan Regency from various aspects such as human resources, budget, and also institution. The method used in this research is a qualitative research method with a case study approach. Data collection was obtained through interviews and document study. This research result shows that Bandung Regency is better prepared and acquainted with Satu Data Indonesia (SDI) policy compared with Kuningan Regency. Although those regions have the same obstacle viz inadequate human resources capacity, Bandung Regency got the budget to do some technical guidance to the regional apparatus organizations to develop the capacity of human resources from data producers. It is hoped that the result of this research can be a study case for the other region in Indonesia who has the same obstacle as a basic search for solutions.